Ternary interpolyelectrolyte complexes insulin-poly(methylaminophosphazene)-dextran sulfate for oral delivery of insulin - Burova, Tatiana V (Langmuir : the ACS journal of surfaces and colloids, 2013)
Ternary interpolyelectrolyte complexes of insulin with biodegradable synthetic cationic polymer, poly(methylaminophosphazene) hydrochloride (PMAP), and dextran sulfate (DS) were investigated by means of turbidimetry, dynamic light scattering, phase analysis, and high-sensitivity differential scanning calorimetry. Formation of ternary insoluble stoichiometric Insulin-PMAP-DS complexes was detected under conditions imitating the human gastric environment (pH 2, 0.15 M NaCl). A complete immobilization of insulin in the complexes was observed in a wide range of the reaction mixture compositions. The ternary complexes were shown to dissolve and dissociate under conditions imitating the human intestinal environment (pH 8.3, 0.15 M NaCl). The products of the complex dissociation were free insulin and soluble binary Insulin-PMAP complexes. The conformational stability of insulin in the soluble complexes of various compositions was investigated by high-sensitivity differential scanning calorimetry. The dependence of the excess denaturation free energy of insulin in these complexes on the PMAP content was obtained. The binding constants of the folded and unfolded forms of insulin to the PMAP polycation were estimated. Proteolysis of insulin involved in the insoluble ternary complexes by pepsin was investigated under physiological conditions. It was found that the complexes ensure an almost 100% protection of insulin against proteolytic degradation. The obtained results provide a perspective basis for development of oral insulin preparations